99mTc-DPD SPECT/CT for localisation of inflammatory and chronic osteoarthritis of the foot and ankle - Stollfuss, Jens C.; Freudenberg, Lutz S.; Wieder, Hinrich (Nuklearmedizin - NuclearMedicine, 2016)
Aim: The precise localisation of osteoarthritic and inflammatory changes is crucial for selective treatment planning of radiosynovectomy (RSV). The present study evaluated the diagnostic accuracy of planar bone imaging and SPECT for the detection of pathological bone metabolism and inflammation in joints of the foot and ankle, compared with SPECT/CT. Patients, methods: 39 patients (mean age 65.6 ± 11.1 years) with suspected inflammatory osteoarthritis underwent SPECT/CT of the feet. After injection of approximately 500 MBq 99mTc DPD, all patients had three-phase planar bone imaging and late-phase hybrid SPECT/CT. late-phase SPECT, and CT of the foot. Increased bone metabolism and blood-pool was assigned to the respective joint of the fore-, mid-, and hindfoot, using SPECT/CT as the reference standard. Results: Overall, SPECT had a higher sensitivity than planar imaging (0.80 vs 0.68, n.s.). The advantage of SPECT was most obvious in the anatomically complex midfoot area (0.63 vs 0.26, p < 0.05) and less obvious in the forefoot (0.85 vs 0.79, n.s.) and hindfoot (0.89 vs 0.89, n.s.). The overall concordance (Cohen`s Kappa) between SPECT/CT and planar (late-phase) imaging and SPECT was high for the forefoot and the hindfoot (planar: 0.78/0.81; SPECT 0.86/0.88) and comparatively low for the midfoot (planar: 0.27; SPECT 0.61). Conclusion: SPECT was significantly superior to planar bone imaging for the detection of joint lesions in the midfoot. The differences between SPECT and planar imaging in the fore- and hindfoot were not significant, most likely due to the inherently less complex anatomy. Compared with SPECT alone, a benefit from the use of SPECT/CT can be observed in the midfoot region where it facilitates the identification of the correct joint for RSV.
Keywords: SPECT/CT; foot and ankle; bone scan; radio-synovectomy